2004
DOI: 10.1021/bi035757s
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Anion Binding in the Substrate Pocket of Bacteriorhodopsin

Abstract: The structure of the D85S mutant of bacteriorhodopsin with a nitrate anion bound in the Schiff base binding site and the structure of the anion-free protein have been obtained in the same crystal form. Together with the previously solved structures of this anion pump, in both the anion-free state and bromide-bound state, these new structures provide insight into how this mutant of bacteriorhodopsin is able to bind a variety of different anions in the same binding pocket. The structural analysis reveals that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…1). This assumption is supported by x-ray diffraction results from a similar BR mutant D85S (34,35). The most prominent modification by this mutation is expected to be an altered electrostatic environment around the retinal.…”
Section: Introductionmentioning
confidence: 74%
“…1). This assumption is supported by x-ray diffraction results from a similar BR mutant D85S (34,35). The most prominent modification by this mutation is expected to be an altered electrostatic environment around the retinal.…”
Section: Introductionmentioning
confidence: 74%
“…However, this situation differs from the anion coordination in the BR mutant D85S. Here, D212 has to be present in the deprotonated state to coordinate the anion (26,27) together with the protonated Schiff base and the hydroxyl of S85 and a water molecule. No coordination was reported with T89 which is also highly conserved among different BRs.…”
Section: Discussionmentioning
confidence: 99%
“…9 Since the protonation state of Asp85 remains unchanged through the N and O intermediates, 41,42 it seems plausible that the conformation of the proton release channel found in M RT Glaeser and his colleagues have recently reported the structures of the D85S mutant of bacteirorhodopsin, which is able to accommodate an anion (chloride, bromide or nitrate) in the vicinity of the Schiff base. 20,43,44 In the presence of halide ions, this mutant exhibits purple. It has been shown that a halide ion binds to the active site and interacts directly with the protonated Schiff base.…”
Section: Crystal Structures Of Bacteriorhodopsinmentioning
confidence: 99%